Strong Converse Inequality for the Meyer-König and Zeller-Durrmeyer Operators (Communications in Mathematical Research, 2021)
In this paper we give a strong converse inequality of type B in terms ofunified $K$-functional $K^α_λ (f, t^2) (0 ≤ λ ≤ 1, 0 < α < 2)$ for the Meyer-König andZeller-Durrmeyer type operators.
Keywords: Meyer-König and Zeller-Durrmeyer type operator; moduli of smoothness; $K$-functional; strong converse inequality; Hölder's inequality.